De novo transcriptomic assembly and profiling of Rigidoporus microporus during saprotrophic growth on rubber wood. (December 2016) - Oghenekaro, Abbot; Raffaello, Tommaso; Kovalchuk, Andriy; Asiegbu, Fred
Abstract Background The basidiomyceteRigidoporus microporus is a fungus that causes the white rot disease of the tropical rubber tree, Hevea brasiliensis, the major source of commercial natural rubber. Besides its lifestyle as a pathogen, the fungus is known to switch to saprotrophic growth on wood with the ability to degrade both lignin and cellulose. There is almost no genomic or transcriptomic information on the saprotrophic abilities of this fungus. In this study, we present the fungal transcriptomic profiles during saprotrophic growth on rubber wood. Results A total of 266.6 million RNA-Seq reads were generated from six libraries of the fungus growing either on rubber wood or without wood.De novo assembly produced 34, 518 unigenes with an average length of 2179 bp. Annotation of unigenes using public databases; GenBank, Swiss-Prot, Kyoto Encyclopedia of Genes and Genomes (KEGG), Cluster of Orthologous Groups (COG) and Gene Ontology (GO) produced 25, 880 annotated unigenes. Transcriptomic profiling analysis revealed that the fungus expressed over 300 genes encoding lignocellulolytic enzymes. Among these, 175 genes were up-regulated in rubber wood. These include three members of the glycoside hydrolase family 43, as well as various glycosyl transferases, carbohydrate esterases and polysaccharide lyases. A large number of oxidoreductases which includes nine manganese peroxidases were also significantly up-regulated in rubber wood. Several genes involved in fatty acid metabolism and degradation as well as natural rubber degradation were expressed in the transcriptome. Four genes (acyl-CoA synthetase, enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase and acyl-CoA acetyltransferase) potentially involved in rubber latex degradation pathway were also induced. A number of ATP binding cassette (ABC) transporters and hydrophobin genes were significantly expressed in the transcriptome during saprotrophic growth. Some genes related to energy metabolism were also induced. Conclusions The analysed data gives an insight into the activation of lignocellulose breakdown machinery ofR. microporus . This study also revealed genes with relevance in antibiotic metabolism (e.g. cephalosporin esterase) as well as those with potential applications in fatty acid degradation. This is the first study on the transcriptomic analysis ofR. microporus on rubber wood and should serve as a pioneering resource for future studies of the fungus at the genomic or transcriptomic level.